A Qualitative Perspective of Strategic Alliances Built From a Study of Malaysian Enterprises. (Journal of International Studies, 2020)
Looking at the rate at which organizations/firms are entering into strategic alliances of late, one can understand and/or appreciate the increased research in the area of strategic alliances. All seek to increase our knowledge and/or understanding of the potentialities, as well as the adversities inherent in the formation of strategic alliances. For Malaysian firms, alliances can provide the means to extend business activity and compete against internationally based competitors. More recently, the Malaysian press has been inundated with news about the emergence of many more such alliances. What is the nature of alliances formed by businesses in Malaysia and how do those alliances contribute to business development? This research first examines theory supporting the classification of alliances in the literature, and then explores managers' perceptions on motivation driving the formation of alliances and the role of alliances in a business's strategic direction. When data identifying the purpose for entering the alliance and benefits received from the alliance were linked to data measuring alliance performance, three major dimensions emerged, which together describe strategic motivation or intent for the range of alliances observed in the data. The framework developed through this research provides a management perspective of building alliances, which supports Sheth and Pravatiyar's (J992) prior classification of strategic (exclusive arrangements that create new opportunities), and operational (enhancing current business capabilities) alliances, with the addition of alliances created to defend past strategic activities against competitive and/or environmental threats.